Problematika Penggunaan Rangka Enhanced Smart Architecture Frame Pada Sepeda Motor yang Cacat Produksi (Studi Kasus Kerusakan Rangka Motor Matic Honda) - Muhammad Rahadian Hasbi; Heru Sugiyono (Jurnal Interpretasi Hukum, 2024)
A problem to the use of Enhanced Smart Architecture Frame (eSAF) in motorcycles that suffer from manufacturing defects. The eSAF framework is an innovation in the motorcycle industry. However, in some cases, defects occur in the frame, which can cause accidents and losses to consumers. This research method uses juridical-normative, by using literature studies of data, positive law, and other legal materials. This research purposes to analyze aspects of consumer legal protection and producer responsibility of the defective eSAF frames with a case study on damaged frames. This research show that consumers who experience accidents due to eSAF frames have not received legal protection as Article 4 of the UUPK hasn’t been fulfilled. Consumers are entitled to receive compensation for losses caused by product use and KUHPer Articles 1504 - 1512 related to defective products. In addition, PT AHM has also not carried out its responsibilities properly, because it has rejected the claims of losses suffered by consumers and withdrawn its products, which is contrary to UUPK Article 7 Jo.. Article 8. Regarding the use of eSAF frames on motorcycles that have production defects, BPKN as government representaion should investigate the case as a step to prevent accidents and provide strict sanctions for business actors who are proven to harm the public as consumers. PT AHM must immediately withdraw all its products that use the eSAF frame as a form of responsibility and compensate for the losses suffered by consumers when accidents occur when using its products.